The potential effect of the updated national criteria on adult cochlear implantation in England and Wales. (4th May 2022) - Constable, James D.; Broomfield, Stephen J.; Romeo, Elisa; Clamp, Philip J.
Abstract : Objectives: Following an update of 'old' TA166 guidance (March 2019), the National Institute for Health and Care Excellence (NICE) predicted a 70% increase in cochlear implantation (CI). We investigated the effect of the 'new' TA566 criteria on adult CI at our regional centre. Methods: Adult CI assessments between 1st January 2015 and 31st December 2018 (before new criteria) and between 7th March 2019 and 31st August 2019 (after new criteria) were retrospectively examined. Calculated eligibility and uptake rates predicted change in annual implantation under the new guidance. Results: 552 patients were identified in the first study period, with a median of 148 assessments per year. Of 533 with complete assessments, 58% were eligible, of whom 74% were implanted. Retrospective application of the new criteria was possible for 277 patients; eligibility and uptake were 67% and 80%, respectively. In the second study period (n = 60), new criteria eligibility was 62% and uptake was 78%. Increased eligibility under the new criteria predicts an increase of between 13 and 23% in annual adult implantation. Conclusions: We demonstrate increased implant eligibility under the latest NICE guidance. Assuming consistent referral patterns, our predicted increase in adult implantation is considerably less than that predicted elsewhere.